Developing Novel Hydroxypropyl-β-Cyclodextrin-Based Nanosponges as Carriers for Anticancer Hydrophobic Agents: Overcoming Limitations of Host-Guest Complexes in a Comparative Evaluation - Shohreh Peimanfard; Ali Zarrabi; Francesco Trotta; Adrián Matencio; Claudio Cecone; Fabrizio Caldera (MDPI AG, 2022)
This study aimed to design and fabricate novel hydroxypropyl-β-cyclodextrin-based hypercrosslinked polymers, called nanosponges, as carriers for anticancer hydrophobic agents and compare them with host-guest complexes of hydroxypropyl-β-cyclodextrin, a remarkable solubilizer, to investigate their application in improving the pharmaceutical properties of the flavonoid naringenin, a model hydrophobic nutraceutical with versatile anticancer effects. For this purpose, three new nanosponges, crosslinked with pyromellitic dianhydride, citric acid, and carbonyldiimidazole, were fabricated. The carbonate nanosponge synthesized by carbonyldiimidazole presented the highest naringenin loading capacity (≈19.42%) and exerted significantly higher antiproliferative effects against MCF-7 cancer cells compared to free naringenin. Additionally, this carbonate nanosponge formed a stable nanosuspension, providing several advantages over the naringenin/hydroxypropyl-β-cyclodextrin host-guest complex, including an increase of about 3.62-fold in the loading capacity percentage, sustained released pattern (versus the burst pattern of host-guest complex), and up to an 8.3-fold increase in antiproliferative effects against MCF-7 cancer cells. Both naringenin-loaded carriers were less toxic to L929 murine fibroblast normal cells than MCF-7 cancer cells. These findings suggest that hydroxypropyl-β-cyclodextrin-based carbonate nanosponges could be a good candidate as a drug delivery system with potential applications in cancer treatment.